A Proposed Novel Stem Cell Therapy Protocol for Liver Cirrhosis. Issue 3 (March 2015) - Lin, Po-Cheng; Chiou, Tzyy-Wen; Lin, Zung-Sheng; Huang, Ko-Chang; Lin, Yi-Chun; Huang, Pi-Chun; Syu, Wan-Sin; Harn, Horng-Jyh; Lin, Shinn-Zong
Currently, there is not an effective therapy for cirrhosis of the liver except for liver transplant. However, finding a compatible liver is difficult due to the low supply and increased demand for healthy livers. Stem cell therapy may be a solution for liver cirrhosis. In our previous report, stem cells from Wharton's jelly and bone marrow were shown to improve liver function in a chemically induced liver fibrosis animal model. However, the immunological rejection of an allograft is always a risk for clinical application. In this study proposal, we suggest using human adipose-derived stem cells (ADSCs) because they are an immune-privileged cell type; they lack human leukocyte antigen-DR expression, and they also suppress the proliferation of activated allogenic lymphocytes and inhibit the production of inflammatory cytokines. In addition, ADSCs contain a sufficient amount of adult stem cells for autologous transplantation. Based on these benefits, ADSCs are promising candidates for clinical application when compared to other stem cell types. The aim of our study will be to investigate the safety and efficacy of autologous ADSCs for the clinical treatment of liver cirrhosis.